Global Alignment and Proportion (GAP) Score: Development and Validation of a New Method of Analyzing Spinopelvic Alignment to Predict Mechanical Complications After Adult Spinal Deformity Surgery. (4th October 2017) - Yilgor, Caglar; Sogunmez, Nuray; Boissiere, Louis; Yavuz, Yasemin; Obeid, Ibrahim; Kleinstück, Frank; Pérez-Grueso, Francisco Javier Sánchez; Acaroglu, Emre; Haddad, Sleiman; Mannion, Anne F.; Pellise, Ferran; Alanay, Ahmet
Abstract : Background: The restoration of normal sagittal alignment is a critical goal in adult spinal deformity surgery to achieve favorable outcomes and prevent mechanical complications. Schwab sagittal modifiers have been accepted as targets for appropriate alignment, but addressing these targets does not always prevent high mechanical complication or revision rates. This may be because the linear absolute numerical parameters do not cover the whole pelvic incidence spectrum and the distribution of lordosis, pelvic anteversion, and negative malalignment are not considered as potential causes of failure. The aim of the present study was to develop and validate a score based on pelvic-incidence-based proportional parameters to better predict mechanical complications. Methods: Two hundred and twenty-two patients (168 women and 54 men) followed for ≥2 years after posterior fusion at ≥4 levels were included in the study. The mean age (and standard deviation) was 52.2 ± 19.3 years (range, 18 to 84 years), and the mean duration of follow-up was 28.8 ± 8.2 months (range, 24 to 62 months). The global alignment and proportion (GAP) score was developed and validated in groups of patients randomly assigned to derivation (n = 148, 66.7%) and validation (n = 74, 33.3%) cohorts. GAP score parameters were relative pelvic version (the measured minus the ideal sacral slope), relative lumbar lordosis (the measured minus the ideal lumbar lordosis), lordosis distribution index (the L4-S1 lordosis divided by the L1-S1 lordosis multiplied by 100), relative spinopelvic alignment (the measured minus the ideal global tilt), and an age factor. Proximal and distal junctional kyphosis and/or failure, rod breakage, and other implant-related complications were considered mechanical complications. The predictive accuracy of the GAP score was analyzed using receiver operating characteristic (ROC) analyses. Associations between GAP categories and mechanical complications and revisions were analyzed using Cochran-Armitage tests. Results: In the validation cohort, 32 patients (43%) experienced mechanical complications and 17 (23%) underwent mechanical revision. The area under curve for the GAP score predicting mechanical complications was 0.92 (standard error [SE] = 0.034, p < 0.001, 95% [confidence interval [CI] = 0.85 to 0.98). Postoperatively, patients with a proportioned spinopelvic state according to the GAP score had a mechanical complication rate of 6% while those with a moderately or severely disproportioned spinopelvic state had rates of 47% and 95%, respectively. Conclusions: The GAP score is a new pelvic-incidence-based proportional method of analyzing the sagittal plane that predicts mechanical complications in patients undergoing surgery for adult spinal deformity. Setting surgical goals according to the GAP score may decrease the prevalence of mechanical complications.